FRI0202 WHAT IS NOT NERVOUS SYSTEM INVOLVEMENT IN BEHÇET SYNDROME: A SURVEY OF PATIENTS WITH BEHÇET SYNDROME REFERRED TO NEUROLOGY. (2nd June 2020) - Dincses, E.; Caliskan, E. B.; Kaya, Z. E.; Uygunoglu, U.; Tutuncu, M.; Saip, S.; Siva, A.; Melikoglu, M.; Hamuryudan, V.; Hatemi, G.
Abstract : Background: Nervous system involvement of Behçet syndrome (neuroBS) is a serious, but infrequent manifestation of Behçet syndrome (BS). Although many BS patients present with signs and symptoms related to the nervous system, several of these are diagnosed with conditions other than neuroBS. The differential diagnosis may be difficult in such patients. Objectives: To identify conditions mimicking neuroBS among patients with BS and to determine clinical, laboratory and imaging findings that may help the differential diagnosis. Methods: We retrospectively screened the charts of 500 BS patients who were registered to our clinic between February 2012 and April 2015, to identify those who were referred to neurology at any time during their follow-up. We follow our BS patients in a multidisciplinary clinic and all patients with a sign or symptom related to the nervous system are seen by one of the neurologist members of the clinic. The final diagnoses, as well as presenting signs and symptoms, laboratory and imaging results and results of any other diagnostic modalities were retrieved from patient charts. Patients who did not have a follow-up visit during the last 3 months were invited to the clinic for their final condition. Those who were not able to come, or one of their family members if they were not able to talk, were interviewed on the phone. Results: Among the 500 BS patients who were screened, 116 (23%) were referred to neurology (53 men, 63 women, mean age 32.8 (±9.8), 98 (84%) fulfilled ISG criteria). Among these, 29 (5.8%) were diagnosed with neuroBS, 30 (6%) had other conditions related to the nervous system, 46 (9.2%) were not diagnosed with a nervous system disorder and their symptoms disappeared and 11 (2.2%) were inconclusive and lost to follow-up. Of the 29 patients with neuroBS, 20 had parenchymal involvement, 7 had cerebral venous sinus thrombosis, 1 had concurrent parenchymal involvement and cerebral venous sinus thrombosis and 1 had atypical neuroBS. Of the 30 BS patients who were diagnosed with another nervous system condition, 14 (2.8%) had primary headache syndromes including tension type headache (n=5) and migraine (n=9), 6 (1.2%) had psychiatric disorders including psychotic disorder (n=1), depression (n=4) and somatization disorder (n=1), the remaining patients had other diagnoses which were entrapment neuropathy (n=2), epilepsy, glial tumor, multiple sclerosis, Meniere's disease, optic neuritis, neuroretinitis, steroid myopathy and polyneuropathy in one patient each. Presentation features such as cerebellar symptoms, motor symptoms, visual problems, altered consciousness, seizure, fever and facial palsy were more common among patients with neuroBS, whereas sensory symptoms and isolated headache were more common among BS patients with other nervous system conditions (Table). Conclusion: Nervous system conditions other than neuroBS are common in patients with BS who present with nervous system findings. Caution is required to avoid misdiagnosis of these patients as neuroBS. Disclosure of Interests: Elif Dincses: None declared, E. Buse Caliskan: None declared, Z. Ece Kaya: None declared, Ugur Uygunoglu: None declared, Melih Tutuncu: None declared, Sabahattin Saip: None declared, Aksel Siva: None declared, Melike Melikoglu: None declared, Vedat Hamuryudan Speakers bureau: Pfizer, AbbVie, Amgen, MSD, Novartis, UCB, Gulen Hatemi Grant/research support from: BMS, Celgene Corporation, Silk Road Therapeutics – grant/research support, Consultant of: Bayer, Eli Lilly – consultant, Speakers bureau: AbbVie, Mustafa Nevzat, Novartis, UCB – speaker